(p+q) (p2-q2) +(p-q) (p2+q2)
Answers
Answered by
50
Heya ✌✌
Here is u r Ans ➡
✨
![= (p + q)(p2 - q2) + (p - q)(p2 + q2) = (p + q)(p2 - q2) + (p - q)(p2 + q2)](https://tex.z-dn.net/?f=+%3D+%28p+%2B+q%29%28p2+-+q2%29+%2B+%28p+-+q%29%28p2+%2B+q2%29)
![= (p + q)(2p - 2q) + (p - q)(2p + 2q) = (p + q)(2p - 2q) + (p - q)(2p + 2q)](https://tex.z-dn.net/?f=+%3D+%28p+%2B+q%29%282p+-+2q%29+%2B+%28p+-+q%29%282p+%2B+2q%29)
![= 2p {}^{2} - 2pq + 2pq - 2p {}^{2}(p - q) \times 4p = 2p {}^{2} - 2pq + 2pq - 2p {}^{2}(p - q) \times 4p](https://tex.z-dn.net/?f=+%3D+2p+%7B%7D%5E%7B2%7D+-+2pq+%2B+2pq+-+2p+%7B%7D%5E%7B2%7D%28p+-+q%29+%5Ctimes+4p+)
![= 2p {}^{2} - 2q {}^{2} + 4p {}^{2} - 4pq = 2p {}^{2} - 2q {}^{2} + 4p {}^{2} - 4pq](https://tex.z-dn.net/?f=+%3D+2p+%7B%7D%5E%7B2%7D+-+2q+%7B%7D%5E%7B2%7D+%2B+4p+%7B%7D%5E%7B2%7D+-+4pq)
![= 6p {}^{2} - 2p {}^{2} - 4pq = 6p {}^{2} - 2p {}^{2} - 4pq](https://tex.z-dn.net/?f=+%3D+6p+%7B%7D%5E%7B2%7D+-+2p+%7B%7D%5E%7B2%7D+-+4pq)
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
Hope This Helps u ☺.
Here is u r Ans ➡
✨
⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐⭐
Hope This Helps u ☺.
captianshoot:
worst answer ever
Answered by
0
Answer:
Correct answer is 2p³-2q³.
Step-by-step explanation:
Hope Thís ïs Hēlpfûl før yõü
Similar questions